Internet-based Spousal Communication during Deployment: Does it Increase Post-deployment Marital Satisfaction? - Warren N. Ponder; Regina T. P. Aguirre (Advances in Social Work, 2012)
The purpose of this study was to explore the question: Is a service member’s post-deployment marital satisfaction correlated with frequency and mode of communication during deployment? This study used an anonymous exploratory design with a sample of 119 Operation Iraqi Freedom (OIF) or Operation Enduring Freedom (OEF) married veterans. Service members who communicated daily during deployment with their spouses had higher marital satisfaction scores than those who communicated less than once per week. Additionally, participants who used US mail had the highest marital satisfaction scores compared to telephone and internet-based communication. This study expands the overwhelmingly qualitative current literature to include quantitative analysis of this topic. This study also depicts the veterans’ experiences since many of the previous studies of this topic used samples of spouses.